Three-Dimensional Biomechanical Analysis of the Bovine Humerus - José Benito Bouza-Rodríguez; Luz Calia Miramontes-Sequeiros (Applied Bionics and Biomechanics)
There are few reports on the biomechanical analysis of the animal humerus. In this study, a three-dimensional finite element model of the bovine humerus was created, and loaded with the physiological forces acting when the cow is falling or jumping (weight and impact forces). Subsequently the corresponding stress and strain distribution in the humerus for different inclined positions of bone was determined.